Phase change materials and nano-enhanced phase change materials for thermal energy storage in photovoltaic thermal systems: a futuristic approach and its technical challenges - Reji Kumar, Rajamony; Mahendran, Samykano; Kumaran, Kadirgama; Pandey, Adarsh Kumar; Tyagi, V. V. (Elsevier, 2020)
In recent years, photovoltaic thermal (PVT) systems have emerged as an imperative research area due to the escalating demand for energy worldwide. Phase change materials (PCMs) considered as the most suitable materials to harvest thermal energy effectively from renewable energy sources. As such, this paper reviews and explains the various aspects of PCM and Nano-Enhanced PCM (NEPCM) integrated PVT systems. The novel and recent developments in PVT research focusing on cooling and thermal energy storage with PCM and NEPCM and their applications in the heating ventilation and air-conditioning (HVAC), building integrated photovoltaic thermal systems (BIPVT), building integrated concentrated photovoltaic thermal systems (BICPVT) are critically summarized. In addition, this review also accentuates the different methods of preparing NEPCM and their thermo-physical properties at different operating temperatures for targeted applications. The present paper also highlights the use of nanofluid, PCM, and NEPCM in extracting the thermal energy from the commercially available for PVT system. In conclusion, this review recapitulates the effort taken by researchers around the world in enhancing the thermal performance system. It is also expected this review will provide greater insight to the new researchers in recognizing the fundamental science behind the development of thermal performance system and the mechanism to enhance further the overall performance of the PVT system.